تطور السلوك الأخلاقي في منظمات الاعمال: مراجعة لأخلاقيات الاعمال عبر الزمن - د. معن وعدالله المعاضيدي; ميسر زهير الطائي (PROSPECTIVE RESEARCHES, 2023)
The present study aims at reviewing the history of behavior conducted by business organizations starting from the industrial revolution until now in order to getting rid of the ethical dilemma, and how this behavior developed a cross the time and the whole obscurities, as well as the environmental conditions. This study ends that businesses ethics have developed positively and have gone with the development of organizations, communities and civil community institutions, depending on egoism or individualism to altruism and not ignoring the interests inside the organization, for doing good deals and serving the community in which it came for it.